2004
DOI: 10.1007/s00127-004-0843-4
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes to depression in urban Turkey

Abstract: In Istanbul, people recognise depression well, but their attitudes towards it are fairly negative. The urban public has unfavourable attitudes towards depression and a tendency to isolate patients from the society. Notwithstanding the high prevalence, there is still considerable stigmatisation associated with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 23 publications
1
7
1
4
Order By: Relevance
“…Finally, the results of this study were surprising in that professional nurses’ attitudes toward mental illness were comparable to attitudes among the general public rather than reflective of professional expertise (Al-Krenawi, Graham, Dean, & Eltaiba, 2004; Angermeyer & Dietrich, 2006; Ozmen et al, 2004; Schomerus et al, 2012; Tsang, Tam, Chan, & Cheung, 2003). One would anticipate that professional training would have an impact on attitudes toward these patients.…”
Section: Discussioncontrasting
confidence: 72%
“…Finally, the results of this study were surprising in that professional nurses’ attitudes toward mental illness were comparable to attitudes among the general public rather than reflective of professional expertise (Al-Krenawi, Graham, Dean, & Eltaiba, 2004; Angermeyer & Dietrich, 2006; Ozmen et al, 2004; Schomerus et al, 2012; Tsang, Tam, Chan, & Cheung, 2003). One would anticipate that professional training would have an impact on attitudes toward these patients.…”
Section: Discussioncontrasting
confidence: 72%
“…People with mental illness require appropriate support to help manage their condition. Stigma associated with mental illness presents significant barriers to this and presents practical, real-life problems for people with mental illness - for example, in finding and keeping work [ 3 ], accessing accommodation [ 4 ] and preventing those with mental illness from seeking professional help [ 34 ]. This study examines the relationship between stigma associated with mental illness and selected demographic and psychosocial factors.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma and discrimination pose significant problems for people diagnosed with mental illness and may lead to real-life disadvantages, including poor access to mental and physical healthcare [ 1 , 2 ], problems gaining or maintaining employment [ 3 ], difficulty accessing accommodation [ 4 ] and reduced life-expectancy [ 5 , 6 ]. Mental illness may also impact negatively on stigmatised individuals by inducing self-stigma , self-judgement and reinforcement of negative stereotypes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in rural areas, it is reported that attitudes may be even more negative and rejection may be even more rampant ( 16 ). According to Ozmen et al there is more stigmatization associated with mental illnesses such as depression in Turkey than in Europe or north America ( 17 ).…”
Section: Discussionmentioning
confidence: 99%